Ethics And Political Behavior In Islam: A Normative And Historical Study Of Islamic Leadership And Governance - Ulil Abshar, Rijal; Yudha, Gesit; Idrus Ruslan (JURNAL TAPIS, 2025)
Corruption, nepotism, identity-based populism, and authoritarianism often erode the moral legitimacy of political institutions. This study aims to identify the fundamental principles of Islamic political ethics and examine their historical implementation during the time of the Prophet Muhammad and the Khulafā’ al-Rāshidīn. These values are then contextualized for modern pluralistic societies such as Indonesia. Using a qualitative approach through a library-based analysis of classical and contemporary Islamic thought, this research finds that Islamic political ethics functions as a moral compass, guiding both leaders and citizens to uphold human dignity, protect communal interests, and reject authoritarianism or opportunism. The historical experience of the Prophet and the Rightly Guided Caliphs highlights ethical governance as a central tenet in Islamic political tradition. In contemporary democratic contexts, the internalization of these ethical values is crucial for fostering inclusive, just, and spiritually grounded political practices.